Pooling adjacent violators under interval constraints - Kopperschmidt, Kai; Stacevičius, Ruslanas (Optimization letters, 2024)
Approaches which “pool adjacent violators” are very simple and efficient methods to solve isotonic regression problems. We extend this type of algorithms to include non-uniform interval constraints in the complete order case. We prove correctness and linear computational complexity of a resulting approach. We also show that a straightforward implementation in C outperforms more general solvers on a sequence of specifically designed problem instances.